Pengaruh pemberian yoghurt sinbiotik tanpa lemak ditambah tepung gembili terhadap kadar kolesterol ldl tikus hiperkolesterolemia - Towil, Afida Soucha; Pramono, Adriyan (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background: Yoghurt is probiotics a fermented milk product, produced by lactic acid bacteria and has being proved tolower cholesterol. The addition lesser yam of inulin could be the hypocholesterolemic effect.Objective:The aim of this study was to analyze the effect of non-fat yoghurt synbiotic added with of lesser yam flouradministration towards LDL cholesterol level in hypercholesterolemic rats.Methods: True experimental study with pre-post test was conducted to 24 male Wistar ratshypercholesterolemiainducedwhich grouped using simple random sampling. Samples was divided into 4 groups by simple random sampling:control, P1 (consumed 2 ml dose), P2 (consumed 3 ml dose), and P3 (consumed 4 ml dose), each group were containedof 6 rats. Non-fat yoghurt synbiotic added with oflesser yam were administered for 14 days intervention. LDLcholesterol level were determined using CHOD-PAP methods. All datas collected were analyzed using paired t-test andOne Way ANOVA followed by LSD test at 95% confidence level.Results: LDL cholesterol level was decreased significantly after 14 days intervention (P1=16.63% (p=0.033);P2=20.72% (p=0.034); P3=20.51% (p=0.013)). P2 was the highest decreasing of LDL cholesterol compared to P3,with the provision of non-fat yoghurt synbiotic added with of lesser yam flour for about 3 ml.Conclusion: Non-fat yoghurt synbiotic added with of lesser yam flour was significant lowering LDL cholesterol level inhypercholesterolemic rats.